2022
DOI: 10.1126/science.abm3425
|View full text |Cite
|
Sign up to set email alerts
|

Immune correlates analysis of the mRNA-1273 COVID-19 vaccine efficacy clinical trial

Abstract: Antibody levels predict vaccine efficacy Symptomatic COVID-19 infection can be prevented by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines. A “correlate of protection” is a molecular biomarker to measure how much immunity is needed to fight infection and is key for successful global immunization programs. Gilbert et al . determined that antibodies are the correlate of protection in vaccinated individuals enrolled in the Moderna COVE phase 3 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
914
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 967 publications
(1,032 citation statements)
references
References 41 publications
36
914
4
Order By: Relevance
“…Nonetheless, Gilbert et al demonstrated that the majority (68.5%) of vaccine efficacy is mediated by neutralizing antibody responses, with the remaining 31.5% of vaccine efficacy may be attributed to cell-mediated responses, other functional antibodies, and innate immunity. 16 These findings are in agreement with studies demonstrating the relationship between neutralizing antibody titers and breakthrough infections. 3,4…”
Section: Scope and Limitationssupporting
confidence: 90%
“…Nonetheless, Gilbert et al demonstrated that the majority (68.5%) of vaccine efficacy is mediated by neutralizing antibody responses, with the remaining 31.5% of vaccine efficacy may be attributed to cell-mediated responses, other functional antibodies, and innate immunity. 16 These findings are in agreement with studies demonstrating the relationship between neutralizing antibody titers and breakthrough infections. 3,4…”
Section: Scope and Limitationssupporting
confidence: 90%
“…Importantly, D614G was dominant over the period of time when the Moderna mRNA-1273 vaccine demonstrated 94% efficacy in preventing symptomatic COVID-19 in the Coronavirus Efficacy (COVE) phase 3 trial (2, 3), making D614G spike protein a primary reference standard. D614G spike binding and neutralizing antibodies also correlated with vaccine efficacy in the COVE study (4), further strengthening the utility of this spike as a reference standard. Notably, D614G is one of the most neutralization-sensitive forms of the virus known to date (5).…”
Section: Textmentioning
confidence: 70%
“…The Omicron variant that was first identified in South Africa in November 2021 is raising concerns because of its increased transmissibility and potential for reduced susceptibility to antibody neutralization attributed to the presence of a large number of spike mutations, including 15 mutations in the receptor binding domain (RBD) that is the major target for neutralizing antibodies (8, 9). To assess the potential risk of this variant to existing vaccines, identical serum samples from participants who received two standard inoculations of mRNA-1273 (100 µg) in the COVE study were tested for neutralization of Omicron in a lentivirus-based pseudovirus assay (4) in two independent laboratories: The Vaccine Research Center (VRC lab) in the National Institutes of Health (NIH), and Duke University Medical Center (Duke lab). One subset of samples from the COVE study was pre-selected as having high titers of neutralizing antibodies against D614G to enable detection of a wide range of titer reductions against Omicron.…”
Section: Textmentioning
confidence: 99%
“…Another report evaluated an immune correlate analysis of the mRNA-1273 COVID-19 vaccine trial and estimated a 90% vaccine efficacy of 57 RBD IgG level of 775 BAU/ml at the time. (12) In this view, even our seropositive HCW would not be protected against symptomatic infection at this moment.…”
Section: Discussionmentioning
confidence: 88%